2011
DOI: 10.3892/ol.2011.360
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference against SPARC promotes the growth of U-87MG human malignant glioma cells

Abstract: Abstract. Malignant glioma is a highly invasive brain tumor resistant to conventional therapies. Secreted protein acidic and rich in cysteine (SPARC) has been shown to facilitate glioma invasion. However, the effects of SPARC on cell growth have yet to be adequately elucidated. In this study, we constructed a plasmid expressing shRNA against SPARC, evaluated the effect of SPARCshRNA on SPARC expression and then assessed its effect on cell growth in U-87MG cells. Using plasmid-delivered shRNA, we effectively su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…SPARC was demonstrated to significantly suppress activation of Akt in hepatic and ovarian carcinoma (35,36). However, SPARC has also been reported to reduce tumor cell apoptosis and promote tumor cell survival by upregulating p-Akt in malignant glioma and melanoma (23,37). In this study, it was observed that Akt pathways, but not ERK pathways, were markedly activated in gastric cancer cells with high levels of expression of SPARC.…”
Section: Discussionmentioning
confidence: 66%
“…SPARC was demonstrated to significantly suppress activation of Akt in hepatic and ovarian carcinoma (35,36). However, SPARC has also been reported to reduce tumor cell apoptosis and promote tumor cell survival by upregulating p-Akt in malignant glioma and melanoma (23,37). In this study, it was observed that Akt pathways, but not ERK pathways, were markedly activated in gastric cancer cells with high levels of expression of SPARC.…”
Section: Discussionmentioning
confidence: 66%
“…Using glioblastoma as an example, SPARC expression has been correlated with increased migration and poor prognosis in humans (235, 236). However, when SPARC expression was inhibited using shRNA, a human cell line showed increased growth and tumorigenic potential (237). The multiple roles played by SPARC in the tumoral environment complicate its use as a biomarker and as a target for therapeutic inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SPARC induced the migration of glioblastoma cell lines (10) and the downregulation of SPARC expression inhibited cell migration and invasion in malignant gliomas (11). However, other studies suggested that SPARC induced endoplasmic reticulum stress leading to autophagy-mediated apoptosis in neuroblastoma (12), and RNA interference against SPARC promoted the growth of malignant glioma cells (13). The aberrant methylation of SPARC was identified in human laryngeal and hypopharyngeal carcinomas (71).…”
Section: Discussionmentioning
confidence: 99%